2015
DOI: 10.1002/nau.22788
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic and functional properties of bulboglandularis striated muscle support its contribution as sphincter in female rabbit micturition

Abstract: Present anatomical and physiological findings support that the Bgm acts as a sphincter during micturition of female rabbits. Neurourol. Urodynam. 35:689-695, 2016. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…This animal has recently been started to be used for the study of the neurophysiology of micturition, as well as for use as an animal model of multiparity-induced damage of the pelvic musculature. 8,9 Our results corroborate previous anatomical findings 10,13-15 and further the knowledge demonstrating that the cutaneous and somatomotor innervation of the perineal region of rabbits is mostly provided by the PDN, which originates from S2 to S3 spinal nerves. Although, previous studies have reported the sacral innervation of rabbits, none of them has described the somatosensory axonal components.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This animal has recently been started to be used for the study of the neurophysiology of micturition, as well as for use as an animal model of multiparity-induced damage of the pelvic musculature. 8,9 Our results corroborate previous anatomical findings 10,13-15 and further the knowledge demonstrating that the cutaneous and somatomotor innervation of the perineal region of rabbits is mostly provided by the PDN, which originates from S2 to S3 spinal nerves. Although, previous studies have reported the sacral innervation of rabbits, none of them has described the somatosensory axonal components.…”
Section: Discussionsupporting
confidence: 91%
“…The present study describes the organization and the somatic composition of the peripheral innervation of pelvic and perineal organs in female rabbits. This animal has recently been started to be used for the study of the neurophysiology of micturition, as well as for use as an animal model of multiparity‐induced damage of the pelvic musculature …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An inapposite reflex activation of pelvic floor muscles, for instance the puborectalis, bulboglandularis, and Pcm, assisting in the storage phase of micturition in female rabbits, 10,22,23 could also affect bladder and urethral pressures. 11 The Pcm assists in the storage phase of micturition, while the Bsm participates in the voiding phase in female rabbits.…”
Section: Discussionmentioning
confidence: 99%
“…In female rats, a similar spinal circuitry responsible for the function of EUS is located caudally to L1 25 . In female rabbit, the bladder and urethral control is located at sacral level, which would be more similar to that in cats and humans in comparison to other species 28‐30 . Indeed, the L6‐S2 VRA damaged have a greater impact more in the Ism than Bsm.…”
Section: Discussionmentioning
confidence: 99%